Concept of Sandhi Sharir in Ayurveda with Modern Correlation (International Journal of Food and Nutritional Sciences, 2022)
According to Ayurveda, knowledge of whole body is important in view of gaining knowledge. Sandhi is explained as “Asthi sanyoga sthaana” that clearly means the meeting point of two or more structures. There are different numbers of sandhis according to different ayurvedic sages.सङ्ख्यातस्तु दशोत्तरे द्वे शते |Sushruta in sharir sthana chapter 5 verse 28 says that there are 210 sandhis1.Types of sandhis and their distribution in body is told in Ayurveda but their sharir rachana is not explained in detail. Nowadays joint disorders and problems are growing day by day. It is a major issue in both domestic and professional life. Hence wholesome knowledge of joints both structurally & functionally is a need of study in todays era from both Nidana & Chikitsa point of view.